Viscoelastic characteristics and phytochemical properties of purple-rice drinks following ultrahigh pressure and pasteurization - Srivilai Worametrachanon (2018)
© 2014 Taylor & Francis. This study investigated how pressure (500, 600MPa/20min) altered the viscoelastic characteristics and phytochemical properties of germinated and non-germinated purple-rice drinks in comparison with pasteurization. Accordingly, color parameters, storage and loss moduli, anthocyanin content, γoryzanol, γaminobutyric acid (GABA), total phenolic compounds and 2,2-diphenyl-1-picrylthydrazyl (DPPH) capacity of the processed drinks were determined. The finding showed that germinated and pressurized rice drink had lower Browning Index than the non-germinated and pasteurized rice drink. The plots of storage and loss moduli for processed rice drinks indicated that time of pressurization had greater impact on gel structural modification than the level of pressure used. The phytochemicals, including total phenolics, and DPPH capacity in pressurized rice drinks retained higher quantity than those in pasteurized drink, despite less treatment effects on anthocyanin. On the contrary, both γoryzanol and GABA were found in high amounts in germinated rice drink with little variation among processing effects.